Aktivitas Antioksidan Krim Hidrofilik Ekstrak Metanol Bunga Cempaka Putih (Magnolia alba) - Ni Nyoman Yudianti Mendra; Dewa Ayu Yunika Pratiwi; Debby Juliadi (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
The white champaca flower (Magnolia alba) holds cultural significance for the Balinese society, being employed in religious ceremonies, adorning bridal setting, and enriching the aroma of incense. Moreover, white champaca flowers contain alkaloids, steroids, terpenoids, flavonoids, and phenols that have antioxidant activity. Therefore, it is interesting to determine the antioxidant activity of methanol extract of white champaca flowers and formulated it into an oil in water cream in this study. The extract was formulated into three cream formulas, FI, FII, and FIII with concentrations of 4, 8, and 12%, respectively. Antioxidant activity was assessed using DPPH (2,2-Diphenyl-1-Picrylhydrazyl) assay with UV-Vis spectrophotometer at a wavelength of 516 nm. The antioxidant activity based on IC50 values for FI, FII, and FIII were 29.72, 25.50, and 25.05 µg/ml, respectively, with IC50 value of vitamin C was 2.93 µg/ml as a standard comparison. The research findings indicate that the methanol extract of white champaca flower o/w cream exhibit a very strong antioxidant activity in vitro. Further research is imperative to investigate the ability of the formulations to delaying the photoaging mechanism through in vivo studies.